Association between air pollutants and blood cell counts in pediatric patients with asthma: a retrospective observational study - Kuo-Chen Huang; Hsiu-Yung Pan; Ting-Min Hsieh; Chih-Cheng Chen; Fu-Jen Cheng (BMC Public Health)
Abstract Background Asthma is a common respiratory disease in children, and air pollution is a risk factor for pediatric asthma. However, how air pollution affects blood cells in pediatric patients with asthma remains unclear. Methods This retrospective observational study, performed in 2007–2018 at a medical center, enrolled non-trauma patients aged < 17 years who visited the emergency department and had asthma. Medical records and blood cell counts, including absolute neutrophil count (ANC), eosinophil count, and platelet count were extracted. The concentrations of PM2.5, PM10, sulfur dioxide (SO2), nitrogen dioxide (NO2), and ozone (O3) were measured from 11 air-monitoring stations in Kaohsiung City. Results One-unit increases in PM2.5 (regression coefficient: 25.618; S.E.: 5.937; p < 0.001), PM10 (19.97; 3.541; p < 0.001), NO2 (70.681; 15.857; p < 0.001), SO2 (81.694; 30.339; p = 0.007), and O3 (23.42; 8.831; p = 0.022) on lag 0–6 (7 d average) correlated positively with ANC. One-unit increases in PM2.5 (0.859; 0.357; p = 0.016), PM10 (0.728; 0.213; p = 0.001), and SO2 (4.086; 1.811; p = 0.024) on lag 0–6 correlated positively with eosinophil count. Additionally, one-unit increases in PM2.5 (0.302; 0.101; p = 0.003) and PM10 (0.229; 0.06; p < 0.001) on lag 0–6 correlated positively with platelet count. In a two-pollutant model, the impacts of PM2.5 and PMC on ANC and platelet count remained statistically significant after adjusting for other air pollutants. Additionally, PMC correlated significantly with eosinophil count after adjusting for PM2.5, NO2, SO2, and O3. Quartile increases in PM2.5 and PMC levels correlated positively with ANC, eosinophil count, and platelet count (all p for trend < 0.05). Conclusions PM2.5, PMC, and NO2 were independently and positively associated with ANC, PMC was positively associated with eosinophil count, and PM2.5 and PMC were positively associated with platelet count in pediatric patients with asthma. Our results highlight the relationship between air pollution and blood cell counts in pediatric patients with asthma.